A study of the eastern nearctic Alloperla (Plecoptera: Chloroperlidae) with hirsute epiprocts using the scanning electron microscope - Baumann, Richard W. (Illiesia, 2009)
Scanning electron microscope images of the epiproct of seven species of eastern Nearctic Alloperla: A. caudata, A. chloris, A. idei, A. petasata, A. voinae, A. vostoki, and A. usa are presented. In the male, these species exhibit an epiproct tip that is covered with short appressed or long, nearly erect hairs.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; Plecoptera; Alloperla; SEM micrographs; USA